Phlox derelicta (Polemoniaceae), a new species in the eastern United States - Floden, Aaron J.; Mckenzie, Patrick (Phytotaxa, 2026)
Phlox derelicta Floden & McKenzie sp. nov. is described for an entity long-recognized and which is shown in molecular phylogenetic data to be distinct from P. glaberrima and instead placed sister to P. ovata and P. pulchra. Here we provide a diagnosis, description, and discussion of its history, its morphology, and distribution in the eastern United States.